74 A web based service for modular SMART on FHIR application development. (22nd November 2019) - Dong, Ziyang; Tang, Qinyi; Yap, Ralf; Bassi, Daiana; Conner, Sue; Fu, Yun; Mohamedally, Dean; Molyneux, Gemma; Roberts, Graham; Sebire, Neil; Booth, John
Abstract : Introduction: Fast Healthcare Interoperability Resources (FHIR), is a standard for exchanging data. It is a common framework that makes it easier to read, write, and transfer medical data, such as patient information securely. SMART is a platform that builds upon the FHIR specification and provides developers with a set of APIs to create applications on top of FHIR. These applications range from retrieving a patient's medication history, to evaluating a patient's risk of cardiac arrest. The aim of this project was to help individual doctors, small teams of developers, or large medical organisations, who may not be familiar with FHIR, to discover the capabilities of SMART APIs and build applications for this next generation of digital healthcare. Method: As part of a joint collaboration between GOSH and UCL computer science (CS), through the industry exchange network programme. CS Students developed a web application using Django, a framework written in Python that employs a model-template-view (MTV) pattern. The client-side templates were built using React. The application's back-end encapsulates the app's logic; and interacts with the data persistency layer- a SQLite database. The code snippets are run by querying the SMART STU3 Sandbox. Results: A functional web application was developed that collates a catalogue of modular SMART functions that a developer can use to implement in their own application. The platform allows non-coders to explore SMART on FHIR components and develop prototype applications. It has a library of runnable code snippets that can act as a helpful tool and reference when building SMART applications. Conclusion: This application supports the development of SMART applications that adhere to FHIR standards in data interoperability, for developers who lack specific knowledge of FHIR standards. Such resources are likely to be of increasing importance as NHS organisations begin to develop customised local programmes using SMART on FHIR.